2019
DOI: 10.52131/joe.2019.0101.0006
|View full text |Cite
|
Sign up to set email alerts
|

Sectorial growth, Exchange rate and Fiscal policy in Developing Economies: The Interlinkages

Abstract: The study examined the interdependence of sectorial growth, exchange rate and fiscal policy by simultaneous equation model for 50 developing economies over the time period of 2000 to 2014. Industrial GDP, service sector GDP, exchange rate, tax revenue are endogenous variables, while capital formation, foreign direct investment, trade, inflation, foreign aid, external debt and money supply are instruments. The study has 4 system of equations and estimated by simultaneous equations models (SEMs) through three-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…In the previous literature, strong evidence of the relationship between corporate governance and investment decision were found. The study of Miloud (2017) concluded that a good corporate governance practices not only link with investment but eventually played its role in business growth (Fazal, Bhatti, & Ahmad, 2019). Similar results consistent with this study are found in the study of Wahyudi and Chairunesia (2019) which aimed to analyze the impact of good corporate governance practices on investment and profitability.…”
Section: Regression Analysissupporting
confidence: 84%
“…In the previous literature, strong evidence of the relationship between corporate governance and investment decision were found. The study of Miloud (2017) concluded that a good corporate governance practices not only link with investment but eventually played its role in business growth (Fazal, Bhatti, & Ahmad, 2019). Similar results consistent with this study are found in the study of Wahyudi and Chairunesia (2019) which aimed to analyze the impact of good corporate governance practices on investment and profitability.…”
Section: Regression Analysissupporting
confidence: 84%
“…The fixed effect and mixed model's technique were used to achieve the objectives of the study. He concluded that trade surplus is positively related with both the GDP per capita of foreign countries and real effective exchange rate and negatively related with foreign direct investment, similar results found by Yang and Shafiq (2020) and Fazal, Bhatti, and Ahmad (2019). Rodrik (2008) points out that for measuring the macroeconomics policy real exchange rate is key factors in case of developing as well as developed nations and it indirectly affects the allocation of resources in the economy like traded and non-traded goods.…”
supporting
confidence: 59%
“…The model uses interval data and covers 10 commodities for 21 nations. Except for the neighboring country, which has a negative sign, all of the coefficients were highly statistically significant (Fazal, Bhatti, & Ahmad, 2019). One of the explanations might be the historical rivalry between Pakistan and India over the prior decades.…”
Section: Literature Reviewmentioning
confidence: 92%